DAMPAK PERUBAHAN PENCATATAN KE PEMBUKUAN PADA WAJIB PAJAK ORANG PRIBADI: STUDI KASUS PROFESI PENGACARA - Yusuf Mulus Riptianto (Politeknik Ubaya, 2023)
The purpose of this study is to compare the impact of changing the obligation to keep records by individual taxpayers to bookkeeping by corporate taxpayers, who are categorized by tax regulations as experts, who are categorized as independent workers, carry out their activities acting for and on their own behalf, not for and on behalf of the association. By studying business processes and taking data on the business circulation of a lawyer practicing in Surabaya, it proves that these changes have had an impact on his tax reporting. For this profession, it is actually obligatory to keep bookkeeping, but it is grouped as a taxpayer who is exempt from the obligation to keep bookkeeping, but is obliged to keep records.